Successful Implementation of Village Fund Policies - Khalimatul Sa'diyah, Salsabilah; Akbar, M. Hikmal; Davita, Sacharissa; Khumayah, Siti; Rahmayanti, Rahmayanti (ann4publisher@gmail.com, 2025)
Background. The Village Fund Policy is not only related to the technical aspects of Village Fund management, but also to the social and cultural aspects of villagers' lives. The success of village financial empowerment through policy is highly dependent on citizen participation and stakeholder cooperation. Aims. This study examines the success of implementing the Village Fund Policy, utilizing Edward III's theory as the analytical framework to address the objective of analyzing the success of the village fund policy, with a focus on Dukuhturi Village, Ketanggungan Subdistrict, Brebes Regency. Methods. The research methodology is a descriptive, qualitative approach, utilizing triangulation of data sources from observation, documentation, and interviews. Result. Effective communication, adequate resources, a positive village disposition, and a coordinated bureaucratic structure support this. Conclusion. The conclusion drawn is that the implementation of the Village Fund Policy in Dukuhturi Village has been optimal, yielding positive impacts on village development and community empowerment. This situation makes Dukuhturi a benchmark for best practices for other villages. Implementation. The implementation of the Village Fund Policy in Dukuhturi Village, as found in the research, aligns with Law Number 6 of 2014 on Villages